The Relationship of Interests in One's Own Education and the Formation of the Ability to Make a Choice in Adolescence - N.P. Shilova (Психолого-педагогические исследования)
The article presents the results of a study of the relationship between the stability of educational interests of boys and girls with awareness of choosing their own future and satisfaction with the choice made in adolescence. The purpose of the study was to identify the relationship between the choice of one's own future and the stability of interests in one's own education. The hypothesis is based on the assumption that satisfaction with the choice of the future is interconnected with a high stability of interests in one's own education. The following methods were used: the electronic version of the "Four Quarters" methodology (authors N.P. Vasilyeva, E.V. Nikitina, B.I. Hasan); the self-determination test (author K. Sheldon, in the version of E.N. Osin); the test "Subjective quality of choosing a training profile" (authors D.A. Leontiev, E.Y. Mandrikova, A.H. Pham). The sample consisted of 686 teenagers and boys/girls from 14 to 21 years old. The analysis showed the relationship between the stability of the choice of compulsory education subjects with a sense of control over one's own life and a sense of conformity of one's own life to oneself. People with high stability of interests have made an independent and voluntary choice, are satisfied with it and feel positive emotions of interest in connection with it with indicators of formed choice since the age of 19. The findings demonstrated that: girls and boys, with a high level of stability of interests among young people aged 19 and over, education allows them to realize that their life as a whole meets their expectations, they have confidence in the independence of their choice and personal control over their lives, they feel satisfaction and positive emotions from what they have done choosing the future.